Calcaneal insufficiency fractures following total knee arthroplasty: Classification and clinical findings. Issue 12 (December 2019) - Yamamoto, Norio; Tsukada, Sachiyuki; Kawai, Jun; Ueda, Daisuke; Noda, Tomoyuki; Ozaki, Toshifumi
Highlights: In this multicentre study, calcaneal IF following TKA was noted in 17 (0.5%) of the 3, 585 patients who underwent primary TKA. Calcaneal IF patients following TKA were significantly shorter and had a significantly higher BMI than calcaneal IF patients without TKA. There were no significant differences in the bone union period or incidence of malunion between cases of calcaneal IF with and without TKA. Abstract: Background: Calcaneal insufficiency fracture (IF) following total knee arthroplasty (TKA) is a rare disorder. This study aimed to examine the prevalence and clinical findings of calcaneal IF following TKA. Methods: We retrospectively reviewed 3, 585 consecutive patients undergoing primary TKA between 2012 and 2017 in four hospitals. Calcaneal IF following TKA was diagnosed by plain radiography or magnetic resonance imaging. First, we investigated the prevalence and clinical findings of calcaneal IF following TKA. Second, we classified calcaneal IF into three types based on its location: type 1, fracture by traction force around the Achilles tendon insertion; type 2, compression fracture around the posterior subtalar joint; and type 3, fracture by ground reaction force at the bottom of the calcaneus. Finally, we compared the clinical findings between calcaneal IF with and without TKA. Results: Calcaneal IF following TKA was seen in 17 (0.5%) of the 3, 585 patients undergoing primary TKA. All patients were female, with a mean age of 76.5 ± 5.9 years, relatively high body mass index (BMI), and osteoporosis. All fractures achieved bone union with conservative treatment. Type 1 fractures were the most common. Calcaneal IFs following TKA were significantly shorter in height and the patients had higher BMI than those without TKA. The locations of calcaneal IF following TKA varied, while only type 1 calcaneal IFs were seen in cases without TKA. However, there were no significant differences with regard to the bone union period or malunion between the two groups. Conclusions: Calcaneal IF should be suspected in patients presenting with ipsilateral foot pain following TKA, particularly in female patients with a relatively high BMI and osteoporosis. Calcaneal IF can be classified into three types based on the fracture location. These variations in calcaneal IF may be due to differences in conditions and changes in mechanical loading of the lower extremity and bone quality following TKA.